Dari prasangka menuju dialog: analisis teks Yohanes 1:35-51 sebagai inspirasi toleransi hidup beragama di Indonesia - Siprianus Soleman Senda; Fladimir Sie; Paternus Raja Mau; Yulianus Minggu (STIPAS Keuskupan Agung Kupang, 2025)
The rise of interreligious prejudice in Indonesia is an alarming phenomenon, evident in the intensification of social polarization, the spread of identity-based conflicts, and the decline of constructive communication among religious communities. This situation often hinders efforts to build truthful narratives and substantive dialogue, as they are obstructed by deeply rooted stereotypes and prejudices. This study analyzes the urgency of an epistemological transformation from prejudice toward authentic dialogue as a concrete embodiment of a dynamic and transformative Christian faith, with a particular focus on the narrative of John 1:35–51. By employing a literature-based methodology and descriptive analysis, this research demonstrates how encounters with Christ provide a strong epistemological and spiritual foundation for overcoming prejudice while fostering meaningful interreligious dialogue. Dialogue in this perspective is not understood as doctrinal relativism but as a praxis grounded in truth, agape love, and mutual recognition. This study specifically examines the application of the principle “come and see” as a methodology for cultivating tolerance in response to the complexities of today’s socio-cultural challenges. By integrating theological reflection with the pluralistic reality of Indonesia, this article offers a new perspective on the contribution of Christians in a plural society, particularly their role as facilitators of dialogue amid a social climate saturated with prejudice. The findings of this research are expected to make a significant contribution to the development of more effective, constructive, and transformative models of interreligious dialogue.